SnO-containing oxide glasses emitting in 1.0–2.0 µm spectral range. (26th April 2018) - Denker, B I; Galagan, B I; Sverchkov, S E; Dianov, E M
Abstract: Different SnO-containing oxide glasses with various net formers (silicate, phosphate, germanate, borate, and a number of mixed compositions) were investigated for the presence of near-infrared photoluminescence. It was found that SnO-containing silicate and germanate, and also a plurality of mixed glass compositions, exhibit wideband photoluminescence peaking at 1.5–1.6 µ m and with lifetimes in the order of 100 µ s. These glasses are interesting as promising active materials for widely tunable fiber lasers and wideband amplifiers.